Cameroon Economic Update, July 2013 : Towards Greater Equity, A Special Focus on Health - World Bank (Washington, DC, 2013)
With these Cameroon economic updates, the World Bank is pursuing a program of short and frequent reports analyzing the trends and constraints in Cameroon's economic development. Each issue, produced bi-annually, provides an update of recent economic developments, as well as a special focus on a topical issue. The Cameroon economic updates aim to share knowledge and stimulate debate among those interested in improving the economic management of Cameroon and unleashing its enormous potential. The notes thereby offer another voice on economic issues in Cameroon, and an additional platform for engagement, learning and exchange. This sixth issue of the Cameroon Economic Updates is entitled 'towards greater equity, a special focus on health'. A results-based approach in health, which provides funding based on results and rewards performance through additional budgetary allocations and bonuses, is currently being piloted in Cameroon. The preliminary results of this approach are encouraging. An extension of this initiative may be an option to improve health services and outcomes, and ensure greater coverage of health services.